Análise de polimorfismos nos genes SOD2, CAT, TNF-alfa e IL-6 em pacientes oncopediátricos com mucosite oral quimioinduzida - Coêlho, Marina de Castro (2021)
Oral mucositis (OM) is a painful inflammatory oral condition caused by chemotherapy in children, with great variability when it comes to how this adverse effect occurs in this population. Oxidative stress is known as a mediator of OM and pro-inflammatory cytokines contribute in the amplification of the immune response, worsening the patient’s oral condition. This study aimed to investigate the frequency of polymorphisms rs4880 (SOD2 47 C/T), rs7943316 (CAT -21 A/T), rs1800629 (TNF-α -308 G/A) and rs1800795 (IL-6 -174 G/C) and their possible associations with chemo-induced OM occurrence and severity in oncopediatric patients. This was an observational, cross-sectional research. Oral epithelial samples from 95 children or adolescents with leukemia or lymphoma submitted to chemotherapy were collected and the genomic DNA was extracted. Singlenucleotide polymorphisms (SNPs) were assessed with PCR-RFLP (Polymerase Chain Reaction - Restriction Fragment Length Polymorphism) and fragments were observed in 6% polyacrilamide gels stained with silver nitrate. Demographic data and information concerning occurrence of OM were obtained from dental charts of the multidisciplinary oral care team. Information on OM severity was limited to the first 60 days of treatment and obtained from appropriately filled OAG registers, in which the score 1 represents absence of oral alterations, score 2 refers to mild to moderate oral alterations, and score 3 corresponds to severe oral mucositis (SOM). Descriptive and inferential statistics were performed with Student’s T test, Chi-squared and Fisher’s Exact tests, with p<0.05. The mean age for the entire sample was 10 yo, and the majority was comprised by male individuals (57.89%). The female sex was considered a protective factor for OM occurrence (RR=0.78; CI [0.64;0.96]) The most common cancer type was acute lymphoblastic leukemia (74.73%). No associations between the SNPs and OM occurrence were detected. For the OM severity analysis, the AA genotype for CAT was more frequent amongst SOM individuals (p=0.04, RR = 1.82; CI = [1.13;2.91]) while the GA genotype for TNF-α was the most frequent amongst individuals without SOM (p=0.03). For SOD and IL-6, the most frequent genotypes were CT and GG respectively for all groups (p>0.05). In conclusion, the AA genotype for rs7943316 could influence OM severity. Due to the impossibility of generating a confidence interval to support the observed associations, data on rs1800629 are inconclusive. OM severity studies with larger sample sizes are encouraged. Genotype combination analysis are still to be carried out. Genetic studies aim unravel the patient’s molecular profile, allowing the development of efficient predictive models and the elaboration of accurate treatment plans.